Acute Appendicitis With Appendiceal Intususseption - N. I. Fetisov; S. S. Maskin; V. V. Matyukhin; J. Yuan (Неотложная медицинская помощь)
Intussusception of the appendix is the introduction of the appendix into the lumen of the cecum may be accompanied by the development of acute appendicitis, or proceed without it. The combination of intussusception and acute inflammation of the appendix makes the diagnosis of appendicitis difficult due to the absence of classic clinical symptoms. The article presents the case of successful treatment of a patient with an untypical clinical presentation of acute appendicitis that developed in an invaginated vermiform appendix.